Study on the Therapeutic Effects of Drug and Cognitive-Behavioral Therapy on Non-Erosive Reflux Disease Patients With Emotional Disorders - Li, Xiuhua; Ding, Fengjiao; Luo, Pandeng; Yang, Jing; Liu, Zhenhua; Liu, Jinwei; Zhang, Yali; Leng, Aimin; Wu, Kuangming (Frontiers in Psychiatry, 2018)
Objective: To assess the correlation between the incidence of NERD and mental and psychological factors, deepen the understanding of the pathogenesis of NERD and explore effective treatments. Methods: NERD patients with mood disorders who met the inclusion criteria were randomly divided into a drug treatment group, a psychotherapy group, and a psychotherapy combined with drug treatment group. Before and after treatment, the patients were retrospectively analyzed using the GERD Questionnaire, Hamilton Depression Scale, Hamilton Anxiety Scale, and SF-36 Quality of Life Scale. Results: All three treatments were found to relieve patients’ symptoms and improve their quality of life to some extent. The psychotherapy combined with drug treatment group showed the best overall curative effect. The Hamilton Depression and Anxiety Scale scores were significantly lower in the psychotherapy-alone group and psychotherapy combined with drug treatment group than in the drug treatment alone group at 4 weeks, 8 weeks, and 12 weeks (P <0.05). Conclusion: Medication, psychotherapy, and psychotherapy combined with medication can relieve clinical symptoms and improve quality of life to varying degrees in patients with NERD.